Electrodeposition of HAp coatings on Ti6Al4V alloy and its electrochemical behavior in simulated body fluid solution. (22nd April 2016) - Dinh, Thi Mai Thanh; Nguyen, Thi Thom; Pham, Thi Nam; Nguyen, Thu Phuong; Nguyen, Thi Thu Trang; Hoang, Thai; Grossin, David; Bertrand, Ghislaine; Drouet, Christophe
Abstract: Hydroxyapatite (HAp) coatings were prepared on Ti6Al4V substrate by electrodeposition method from electrolyte solution containing Ca(NO3 )2, NH4 H2 PO4 and NaNO3 . The results show that the HAp coatings were single phase crystals of HAp. Scanning electron microscope (SEM) images present that HAp/Ti6Al4V have flake shapes which arrange to form like-coral agglomerates. In vitro test of the Ti6Al4V and HAp/Ti6Al4V in simulated body fluid (SBF) solution was investigated with different immersion times. pH of SBF solution decreased and the mass of materials increased. SEM images prove the formation of apatite on the surface of Ti6Al4V and HAp/Ti6Al4V. The corrosion current density during immersion time of substrate is always higher than the one of HAp/Ti6Al4V because the deposited HAp can protect well for the substrate.